La participación política en la escuela como alternativa a la cultura del silencio. (2017)
After questioning political participation and education in school, thispaper reviews different authors and notions such as negative freedom andepistemology of feeling, which help to remove the suppositions of silencing,obedience and discipline of the bodies. As a way to encourage the collectiveconstruction of a more just and egalitarian society, the final part of the paperpresents a pedagogical proposal based on the creation of communicativescenarios that allow recovering the voices of young students and their teachers.